The Impact of Incomplete Faces of Spokes-Characters in Mobile Application Icon Designs on Brand Evaluations - Ning, Zhang; Chunqun, Liu; Zelin, Tong; Nan, Zhou; Yiting, Hu (Frontiers in Psychology, 2020)
In this article, we explore how incomplete spokes-character faces (versus complete spokes-character faces in application icon designs) make a positive impression on users, and we outline the boundary conditions. Across three studies, we find incomplete spokes-character faces to be an effective image icon tool. In study 1, we find that spokes-characters with incomplete faces improve users’ brand evaluations. In study 2, we find that incomplete spokes-character faces create perceptions of anthropomorphism, which lead to more favorable brand evaluations by enhancing the interpersonal closeness between the user and the brand. The results of study 3, however, show that the type of social exclusion (control vs. ignored vs. rejected) moderates the relationship between incomplete spokes-character faces in mobile application icons and brand evaluations.